6n-6(5-n)=36+n

Simple and best practice solution for 6n-6(5-n)=36+n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6n-6(5-n)=36+n equation:


Simplifying
6n + -6(5 + -1n) = 36 + n
6n + (5 * -6 + -1n * -6) = 36 + n
6n + (-30 + 6n) = 36 + n

Reorder the terms:
-30 + 6n + 6n = 36 + n

Combine like terms: 6n + 6n = 12n
-30 + 12n = 36 + n

Solving
-30 + 12n = 36 + n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-1n' to each side of the equation.
-30 + 12n + -1n = 36 + n + -1n

Combine like terms: 12n + -1n = 11n
-30 + 11n = 36 + n + -1n

Combine like terms: n + -1n = 0
-30 + 11n = 36 + 0
-30 + 11n = 36

Add '30' to each side of the equation.
-30 + 30 + 11n = 36 + 30

Combine like terms: -30 + 30 = 0
0 + 11n = 36 + 30
11n = 36 + 30

Combine like terms: 36 + 30 = 66
11n = 66

Divide each side by '11'.
n = 6

Simplifying
n = 6

See similar equations:

| 11-2x=5x+x | | -9x+x=4-6 | | 2079=2x+2(2x-5)+2(5x+10) | | 2/3(-9) | | 44=20 | | 2.5x-7=4x+19 | | 8(v+4)=24+8v | | -6p=3p | | v+2/v-1=7/2 | | 5x+2x-3+5=48 | | 5/9*18/1 | | -4x^2=-5x+8 | | 0.5(x+20)+0.9=59 | | 36.9=3.7b-16.9 | | H=at-0.25vt*2 | | k-6=2 | | 7x+5=10x+3 | | 65=5b | | 5/9(18) | | 5(m+4)+3m=18+8m | | 3+1x=7 | | 3-1x=7 | | 3/5y^2+1/5y=4/5 | | 3x+4-5x=9x-3 | | 2x-x=3+2x | | 8/2=x/x-3 | | 0.8x+4.7=1.9 | | w/5-7=-6 | | 2/5n+200=8400 | | 4=m-3 | | 10x-7=-7+4x | | 2/3j=12 |

Equations solver categories